Challenges and Opportunities for Islamic Education Teachers in Madrasah Ibtidaiyah in the Era of the Industrial Revolution 5.0 - iqbal tawakkal (Badan Usaha Milik Desa Berkaho Pungpungan, 2025)
This study explores the challenges and opportunities faced by Islamic Education teachers (PAI) at Madrasah Ibtidaiyah (MI) in the context of the Industrial Revolution 5.0. As education shifts towards integrating advanced technologies with human-centered values, teachers are required not only to master pedagogical skills but also to adapt to digital innovations that influence learning environments. Using a Systematic Literature Review (SLR) approach, this research analyzes relevant studies published between 2018 and 2024 to identify emerging themes, strategies, and implications for Islamic education. The findings reveal that teachers face substantial challenges, including digital literacy gaps, limited access to modern facilities, and the growing influence of globalization on students’ values and behavior. However, significant opportunities also arise, such as the integration of digital platforms, innovative pedagogical approaches, and the possibility of fostering both academic competence and noble character simultaneously. Moreover, the study highlights that PAI teachers serve as moral agents who must ensure that technological advancement does not compromise spiritual and ethical development. The novelty of this research lies in providing a comprehensive mapping of how Islamic education at the elementary level can respond to Industrial Revolution 5.0 by combining tradition with innovation. In conclusion, strengthening teacher competence through professional development, policy support, and contextualized digital integration is essential to sustain the relevance and transformative role of Islamic education in this era.